Sherlock Holmes short stories - West, Clare (Oxford University Press, 2000)
Sherlock Holmes is the greatest detective of them all. He sits in his room, and smokes his pipe. He listens, and watches, and thinks. He listens to the steps coming up the stairs; he watches the door opening - and he knows what question the stranger will ask. In these three of his best stories, Holmes has three visitors to the famous flat in Baker Street - visitors who bring their troubles to the only man in the world who can help them